Exploring the link between experienced teachers' learning outcomes and individual and professional learning community characteristics. Issue 2 (2nd April 2016) - Vanblaere, Bénédicte; Devos, Geert
Abstract : The continuous professional development of teachers is crucial in our current knowledge-based society, yet empirical research on experienced teachers' learning outcomes is scarce. In this study, we examine perceived changes in classroom practices and in competence as outcomes. By making these outcomes measurable, we can relate them to several individual teacher characteristics and professional learning community characteristics. A questionnaire was administered to 490 experienced teachers from 48 Flemish (Belgian) primary schools. Multilevel analyses show that of the professional learning community characteristics, only reflective dialogue is significant for perceived changes in practices. As for individual characteristics, self-efficacy relates positively to both perceived changes in practices and in competence. The relationship between teaching experience and both learning outcomes, however, is negative.